Edukasi Partisipatif Bahaya Merokok Untuk Meningkatkan Pengetahuan Dan Mencegah Perokok Pemula Di SMP Sima Kota Padang - Wira Iqbal; Kamal Kasra; Frima Elda; Aria Gusti; Fadilla Azmi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Adolescent smoking behavior remains a significant public health issue, contributing to the increased risk of non-communicable diseases and reduced quality of life. Schools play a strategic role as a locus for educational interventions in smoking prevention. This community service activity aimed to enhance the knowledge and awareness of students at SIMA Junior High School, Padang, regarding the dangers of smoking through a school-based education program. The method employed was a participatory community-based approach involving 30 students. The program consisted of socialization, interactive counseling, and the distribution of educational media in the form of an educational video. Evaluation was conducted using pre-test and post-test to measure changes in students’ knowledge before and after the intervention. The results showed an increase in the mean knowledge score from 71.99 in the pre-test to 76.0 in the post-test. A paired t-test yielded p=0.002 (<0.05), indicating a statistically significant improvement in students’ knowledge about the dangers of smoking after the intervention. Although the distribution of the “high knowledge” category slightly decreased, the overall increase in mean scores suggests that the educational program effectively strengthened students’ understanding. In conclusion, the school-based educational program proved effective in improving students’ knowledge about the dangers of smoking. Program sustainability requires periodic updating of educational materials and active collaboration among schools, teachers, parents, and the community. Such efforts are expected to prevent the emergence of novice smokers and support the establishment of a healthy, smoke-free school environment.